What Drives the Stock Market Integration in the CEE-3? - Tomas Vyrost; Eduard Baumöhl; Stefan Lyocsa (Ekonomicky casopis/Journal of Economics, 2013)
In this article, we study the possible explanatory power of macroeconomic factors that may drive the stock market integration between the Czech Republic, Poland and Hungary (CEE-3) and developed countries, using Germany as a benchmark. Our findings suggest that the recent global financial crisis has affected time-varying correlations between certain stock markets more substantially than the entry of the CEE-3 into the EU. The results of our analysis of the effects of these macroeconomic factors were inconclusive. Only our proxy of exchange rate risk was significant in all cases, with positive effects on integration, thus supporting the presence of contagion among different markets.
Keywords: G01; G15; C32; 330; stock market integration; CEE-3; time-varying correlations; DCC MV-GARCH model; macroeconomic factors